2020
DOI: 10.3390/min10090792
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeochemical Study on Closed-Basin Lakes in Cold and Semi-Arid Climates of the Valley of the Gobi Lakes, Mongolia: Implications for Hydrology and Water Chemistry of Paleolakes on Mars

Abstract: Previous studies suggested that, generally, the climate of early Mars would have been semi-arid when the surface temperatures were above freezing. On early Mars, closed-basin lakes would have been created; however, the hydrogeochemical cycles of the lake systems are poorly constrained. Here we report results of our field surveys to terrestrial analogs of closed-basin lake systems that developed in cold and semi-arid climates: The Valley of the Gobi Lakes of Mongolia. Our results show that groundwater plays a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Our previous study investigated the hydrology around Orog and Olgoy lakes through field surveys in warm seasons (Sekine et al., 2020). Based on this previous study, the major water source of Orog Lake during summer is the Tuin River, along with underground water flow along the river and local springs (Sekine et al., 2020). In the surveys of the present study, the surface of the Tuin River was completely frozen.…”
Section: Study Area and Methodologymentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous study investigated the hydrology around Orog and Olgoy lakes through field surveys in warm seasons (Sekine et al., 2020). Based on this previous study, the major water source of Orog Lake during summer is the Tuin River, along with underground water flow along the river and local springs (Sekine et al., 2020). In the surveys of the present study, the surface of the Tuin River was completely frozen.…”
Section: Study Area and Methodologymentioning
confidence: 99%
“…However, we found that a small input of underground water occurs along the river into the central Orog Lake, even in February. The major water source of Olgoy Lake during summer is local springs, which originates melting of permafrost (Sekine et al., 2020). In the surveys of February 2019 and January 2020, we recorded no significant inputs of spring water into Olgoy Lake due to the low temperatures (−20°C).…”
Section: Study Area and Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…The formation constants from Asp 2− of all the dissolved and adsorbed AspAsp species were calculated by setting the logK value for the zwitterionic Asp dimerization in water (i.e., Asp ± + Asp ± → AspAsp ± + H 2 O) to -3.0 [16] and by combining this value with the respective AspAsp protonation and adsorption constants (Table A4). The examined pH and NaCl concentrations were 3-10 (5-10 for γ-alumina) and 1-100 mM, respectively, corresponding to a range of natural waters in rivers, soil, terrestrial springs, saline lakes, and rainfall [63][64][65][66][67]. There is no definitive constraint on the α-amino acid abundance in primitive environments.…”
Section: Thermodynamic Prediction Of Asp Dimerization At the Mineral-water Interfacementioning
confidence: 99%